2011
DOI: 10.1074/jbc.r110.197046
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Asthma: Influence of Genetic and Environmental Factors

Abstract: Allergic asthma is a chronic airway inflammatory disease in which exposure to allergens causes intermittent attacks of breathlessness, airway hyper-reactivity, wheezing, and coughing. Allergic asthma has been called a "syndrome" resulting from a complex interplay between genetic and environmental factors. Worldwide, >300 million individuals are affected by this disease, and in the United States alone, it is estimated that >35 million people, mostly children, suffer from asthma. Although animal models, linkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
93
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 90 publications
0
93
0
1
Order By: Relevance
“…The hallmarks of asthma include allergic airway inflammation, bronchial hyper-responsiveness, mucus hyperplasia and airway remodeling (2). It has been shown that asthma is a complex disease that results from interactions between environment and genetic factors (3)(4)(5). The associations between the risk of asthma and gene polymorphisms, such as single nucleotide polymorphism (SNPs), have been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…The hallmarks of asthma include allergic airway inflammation, bronchial hyper-responsiveness, mucus hyperplasia and airway remodeling (2). It has been shown that asthma is a complex disease that results from interactions between environment and genetic factors (3)(4)(5). The associations between the risk of asthma and gene polymorphisms, such as single nucleotide polymorphism (SNPs), have been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…The hallmarks of asthma are airway inflammation, remodeling and hyperresponsiveness (2,15). The UGRP1 gene was identified by Niimi et al (4), and is located in a chromosomal region harboring a number of genes involved in allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Over 300 million individuals are affected by asthma worldwide, of which there are at least 35 million patients in the United States alone. [1] COPD is highly prevalent and a significant cause of morbidity and mortality, which affects more than 200 million people globally. [2] It is expected to be the third leading cause of death worldwide in 2020.…”
mentioning
confidence: 99%